Impact mechanism of inclusive leadership on employees’ workplace wellbeing in service enterprises: a chain mediation model of relational identification and job embeddedness - Yang, Zhuquan (Frontiers in Psychology, 2025)
In service enterprises, employees’ workplace wellbeing is not only crucial for individual performance and mental health, but also directly affects organizational stability and customer satisfaction. Drawing on social identity theory (SIT), this study constructs and tests a chain mediation model in which inclusive leadership influences employees’ workplace wellbeing through relational identification and job embeddedness. Based on a questionnaire survey of 386 frontline employees in service enterprises in South China, the study employs structural equation modeling (SEM) and bootstrapping analysis. The results show that: (1) inclusive leadership has a significant positive effect on employees’ workplace wellbeing; (2) relational identification and job embeddedness do not exert significant mediation effects when considered independently; (3) relational identification enhances workplace wellbeing significantly through increased job embeddedness, forming a valid chain mediation path; and (4) gender plays a moderating role in some paths, with male employees relying more on structural embeddedness for wellbeing and female employees being more influenced by emotional identification. This study reveals the underlying psychological mechanism by which inclusive leadership enhances workplace wellbeing, enriching the literature on leadership and employee psychological wellbeing, and providing practical guidance for optimizing employee management strategies in service enterprises.